How environmental patents, education, and energy transition impact greenhouse gases: evidence from E7 countries - Zhang, Bing; Wang, Yujing; Liu, Mingyang; Mehmood, Usman (Frontiers in Environmental Science, 2025)
Mitigating greenhouse gas emissions (GHG) is crucial to achieving sustainable development and ensuring a prosperous and environmentally sound future. This study is motivated by the pressing need to address the environmental challenges faced by the E−7 economies—Brazil, India, Indonesia, Russia, Mexico, China, and Turkey—due to their rapid economic transitions and significant contributions to global GHG emissions. It investigates the long-term impact of environmental patents (ENP), financial development (FD), energy transition (ENT), and education (EDU) on GHG in the E−7 nations using second-generation econometric methods, including momentum quantile regression (MMQR), over the period 1990–2019. It also investigates the moderating effects of FD on ENT and EDU in influencing GHG emissions. The results reveal that ENT and ENP reduce GHG emissions across all quantiles, with ENT’s effect stronger at lower quantiles and ENP’s influence intensifying at higher quantiles. EDU shows a consistent positive impact on GHG across quantiles, reflecting its role in driving industrialization and energy demand, while FD reduces GHG emissions significantly at higher quantiles, supporting its role in green investments. Interaction terms indicate that FD enhances the impact of ENT in reducing GHG emissions but moderates EDU’s effect in a way that can either amplify or offset emissions depending on the context. The robustness analysis validates these findings, particularly for ENT and FD, and highlights EDU’s potential for emissions reduction under specific conditions. These findings emphasize the need for targeted policies that leverage ENT and ENP for emissions reduction, strategically direct FD toward sustainable investments, and manage the dual role of EDU in emissions dynamics. This study offers critical insights for policymakers in the E−7 nations to balance economic growth with environmental sustainability, contributing to global efforts to combat climate change.